Calcium-calpain Dependent Pathways Regulate Vesiculation in Malignant Breast Cells - Taylor, Jack; Jaiswal, Ritu; Bebawy, Mary (Current Cancer Drug Targets, 2017)
Background: Multidrug resistance in cancer (MDR) occurs when tumours become crossresistant to a range of different anticancer agents. One mechanism by which MDR can be acquired is through cell to cell communication pathways. Membrane-derived microparticles (MPs) are emerging as important signaling molecules in this process. MPs are released from most eukaryotic cells and transfer functional proteins and nucleic acids to recipient cells conferring deleterious traits within the cancer cell population including MDR, metastasis, and angiogenesis. MP formation is known to be dependent on calpain, an intracellular cysteine protease which acts to cleave the cytoskeleton underlying the plasma membrane, resulting in cellular surface blebbing Objective: To establish the role of calpain in vesiculation in malignant and non-malignant cells by 1) comparing membrane vesiculation at rest and following the release of intracellular calcium, and 2) comparing vesiculation in the presence and absence of calpain inhibitor II (ALLM). Method: This study examines the differences in vesiculation between malignant and non-malignant cells using high-resolution Atomic Force Microscopy (AFM). HBEC, MBE-F, MCF-7, and MCF- 7/Dx cells were analysed at rest and following treatment with calcium ionophore A23187 for 18 hours. Vesiculation of calcium activated and resting malignant and non-malignant cells was also assessed after 18 hour treatment of calpain inhibitor II (ALLM). Results: We demonstrate that malignant MCF-7 and MCF-7/Dx cells have an intrinsically higher degree of vesiculation at rest when compared to non-malignant human brain endothelial cells (HBEC) and human mammary epithelial cells (MBE-F). Cellular activation with the calcium ionophore A23187 resulted in an increase in vesiculation in all cell types. We show that calpain-mediated MP biogenesis is the dominant pathway at rest in malignant cells as vesiculation was shown to be inhibited with calpain inhibitor II (ALLM). Conclusion: These results suggest that differences in the biogenic pathways exist in malignant and non-malignant cells and have important implications in defining novel strategies to selectively target malignant cells for the circumvention of deleterious traits acquired through intercellular exchange of extracellular vesicles.
Keywords: Atomic force microscopy